\[\boxed{\text{1203\ (1203).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[n(n + 1)(n + 2)(n + 3) + 1 =\]
\[= n(n + 3)\left( n^{2} + 2n + n + 2 \right) + 1 =\]
\[= \left( n^{2} + 3n \right)\left( n^{2} + 2n + n + 2 \right) + 1 =\]
\[+ 1 = \left( n^{2} + 3n + 1 \right)^{2} - 1^{2} + 1 =\]
\[= \left( n^{2} + 3n + 1 \right)^{2} - 1 + 1 =\]
\[= \left( n^{2} + 3n + 1 \right)^{2}\ \]
\[\boxed{\text{1203.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = 3;\]
\[(3;0);\ \ (0;2)\]
\[y = kx + b\]
\[2 = 0 + b \Longrightarrow \ \ b = 2\]
\[0 = 3k + 2\]
\[k = - \frac{2}{3} \Longrightarrow \ \ y = - \frac{2}{3}k + 2;\]
\[(1;0);\ \ (0;\ - 3)\]
\[y = kx + b\ \ \]
\[- 3 = 0 + b\ \ \Longrightarrow b = - 3\]
\[0 = k - 3\ \ \]
\[k = 3 \Longrightarrow \ \ y = 3x - 3.\]